KOMUNIKASI PROFETIK RASULULLAH DALAM MEMBANGUN UKHUWWAH DI MADINAH - Mukoyimah Mukoyimah (Islamic Communication Journal, 2019)
Communication is a core activity in every interaction. Every interaction contains a vision, so does the Prophet Muhammad. as a communicator. Prophetic communication of the Prophet needs to be an example/uswatun hasanah in building ukhuwwah. This study aims to provide an understanding back to the communicator/da'i of the current era about what prophetic communication should be done in facing of the complex conditions in the middle of the communicant. This research is a qualitative library research on hadiths delivered by the Prophet in Medina. While the data collection techniques is documentation and the data analysis used is interpretation. The results of this study shows the prophetic communication built on the personal and communal understanding of communicant, giving rise to the right method and way to build ukhuwwah in Medina. The communication of Rasulullah was carried out clearly, repeating the message of da'wah, and adjusting the capability of the mad'u/communicant faced so that the Islamic community's ukhuwwah was well developed.Â